Expression of matrix metalloproteinases and their inhibitors in the woodchuck model of hepatocellular carcinoma. Issue 7 (17th April 2013) - Ochoa‐Callejero, Laura; Toshkov, Ilia; Menne, Stephan; Martínez, Alfredo
Abstract Matrix metalloproteinases (MMPs) play a central role in tumor invasion and metastasis. Increased expression of MMPs occurs during development of hepatocellular carcinoma (HCC) in humans following infection with hepatitis B virus (HBV). Woodchucks are used as an animal model for hepadnavirus‐induced HCC. All woodchucks infected chronically with woodchuck hepatitis virus (WHV), a virus that is closely related to HBV, develop HCC. In the present study MMPs and related molecules were investigated in woodchucks to better understand the mechanisms of extracellular matrix remodeling in HCC. Three groups of samples were studied: liver and HCC tissues from animals infected with WHV and age‐ and gender‐matched normal liver from animals not infected with WHV. New partial gene sequences for woodchuck MMP‐2, MMP‐7, and MMP‐9 as well as their inhibitors NGAL, TIMP‐1, and TIMP‐2 were identified and used for determination of expression levels in liver and HCC by qRT‐PCR. Compared to liver of WHV‐naïve woodchucks, high levels of MMP‐1, MMP‐2, MMP‐7, NGAL, and TIMP‐1 were detected in liver of animals infected with WHV. However, no differences were found for TIMP‐2. MMP‐9 expression was higher in HCC than in liver of animals not infected with WHV. Immunohistochemical staining demonstrated that MMP‐9 immunoreactivity was most intense in HCC, correlating with the progression of liver disease. Upregulation of MMP‐9 in HCC was confirmed by Western blotting and zymography analysis. Furthermore, the activity of woodchuck MMPs was suppressed by BiPS, a common inhibitor of mammalian MMPs. These results suggest the use of MMP inhibitors as a potential HCC treatment strategy that could be explored in woodchucks. J. Med. Virol. 85:1127–1138, 2013. © 2013 Wiley Periodicals, Inc.